The Use of Motivational Word Translation Posters in Learning Vocabulary for Grade X Students at MA Jabal Nur - Tizrah, Afrinda; Sujatmiko, Sujatmiko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study aims to: (1) find out students' perceptions of the use of motivational word translation posters in vocabulary learning at MA Jabal Nur; and (2) determine the translation techniques used in the use of poster translation of motivational word. This research used a qualitative method where the data collection was done by observation, interview, and documentation so that it could explore more deeply related problems found at MA Jabal Nur about the limited vocabulary of students. The subjects of this research are students in grade X at MA Jabal Nur. The object of this research is to use English language learning to increase students' vocabulary by using motivational word translation posters that are pasted all over the walls of MA Jabal Nur classrooms. The results of this study indicate that it can have a positive influence on students at MA Jabal Nur NTT. They were 19 students said it was very helpful to increase student vocabulary, and 1 student is quite difficult to memorize because he forgets quickly, but after the poster media posted by the researcher, it took days to remember the vocabulary he read repeatedly. While one student finds it difficult to understand learning English, the student is quite capable of recognizing English vocabulary, but knowing or memorizing the source language is very difficult for him. As for the techniques used in the translation poster media, among others: Established equivalence techniques as much as 223 or around (78.0%), while amplification techniques as much as 20 or around (7.0%). Pure borrowing technique as much as 4 about (1.4%) and natural borrowing 3 about (1.0%)